9514 1404 393
Answer:
y = 3x +3
Explanation:
The midpoint of the given segment is a point on the line. That point is ...
M = ((7, 4) +(-5, 8))/2 = (7-5, 4+8)/2 = (1, 6)
The difference between the end points can be helpful in writing the equation.
(-5, 8) -(7, 4) = (-12, 4) = (Δx, Δy)
Then the general form of the equation of the perpendicular bisector can be written as ...
Δx(x -Mx) +Δy(y -My) = 0 . . . . . where midpoint M = (Mx, My)
-12(x -1) +4(y -6) = 0
Dividing by -4 and eliminating parentheses, we have ...
3(x -1) -(y -6) = 0
3x -y +3 = 0 . . . . general form equation for the line
y = 3x +3 . . . . . . slope-intercept form equation